Serum S100B and intelligence in children with Down syndrome - Nurul Noviarisa; Eva Chundrayetti; Gustina Lubis (Indonesian Pediatric Society Publishing House, 2019)
Background Down syndrome is characterized by physical and mental retardation and caused by chromosome 21 (Hsa21) abnormalities. The S100B is a protein that is overproduced in Down syndrome due to overexpression of chromosome 21 genes. Comorbidities caused by S100B in Down syndrome are cognitive deterioration and early onset of dementia. Objective To assess for a possible association between S100B protein and intelligence levels in children with Down syndrome. Method This cross-sectional study included students in a special needs school in Padang, West Sumatera, who had the characteristic clinical features of Down syndrome and trisomy 21 by chromosome analysis. Examination of S100B levels was carried out using an enzyme-linked immunosorbent assay (ELISA) method. Intelligence quotient (IQ) was measured using the 4th edition of the Wechlser Intelligence Scale for Children (WISC-IV) method. Results A total of 39 children with Down syndrome participated in the study. There were 25 children with mild mental retardation and 15 children with moderate-severe mental retardation. The mean S100B levels were not significantly different between groups [479.1 (SD 204) pg/mL in the mild mental retardation group and 458.7 (SD 158) pg/mL in the moderate-severe mental retardation group; P > 0.05]. The mean S100B level was significantly higher in subjects aged ≤ 10 years than in those aged > 10 years [566.9 (SD 210.0) pg/mL and 434.4 (SD 167.2) pg/mL, respectively (P<0.05)]. Conclusion There is no association between S100B and intelligence levels in children with Down syndrome. There is a significant association between higher S100B levels and younger age in children with Down syndrome.